Topical calcineurin inhibitors in systemic lupus erythematosus - Christos E Lampropoulos; David P D’Cruz (Dove Medical Press, 2010)
Christos E Lampropoulos, David P D’CruzLupus Research Unit, Rayne Institute, St. Thomas’ Hospital, London, UKAbstract: Cutaneous lupus erythematosus (CLE) encompasses a variety of lesions that may be refractory to systemic or topical agents. Discoid lupus erythematosus (DLE) and subacute cutaneous lupus erythematosus (SCLE) are the most common lesions in clinical practice. The topical calcineurin inhibitors, tacrolimus and pimecrolimus, have been used to treat resistant cutaneous lupus since 2002 and inhibit the proliferation and activation of T-cells and suppress immune-mediated cutaneous inflammation. This article reviews the mechanism of action, efficacy, adverse effects, and the recent concern about their possible carcinogenic effect. Although the total number of patients is small and there is only one relevant randomized controlled study, the data are encouraging. Many patients, previously resistant to systemic agents or topical steroids, improved after four weeks of treatment. DLE and SCLE lesions were less responsive, reflecting the chronicity of the lesions, although more than 50% of patients still showed improvement. Topical calcineurin inhibitors may be a safe and effective alternative to topical steroids for CLE although the only approved indication is for atopic dermatitis.Keywords: tacrolimus, pimecrolimus, cutaneous lupus erythematosus, topical calcineurin inhibitors